Representasi Visual Kesehatan Mental pada Film Dear David - Marcel Maulana; Yulianti (UNISBA Press, 2023)
Abstract. Film as a visual art form greatly influences people's perception of various issues, including mental health. Mental health issues have become increasingly important worldwide, with over 300 million people suffering from depression and over 260 million people experiencing anxiety disorders, according to the World Health Organization (WHO). However, mental health problems are often ignored or considered taboo by many societies. In recent years, there has been a significant increase in the number of cases of mental health disorders and stress caused by the complexity of life and high social expectations. Films can serve as a powerful tool in shaping people's perceptions and attitudes towards mental health issues.This research aims to examine the representation of mental health in films, particularly in the film